The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1979
DOI: 10.1111/j.1600-0560.1979.tb01111.x
|View full text |Cite
|
Sign up to set email alerts
|

Giant Cells in Male Pattern Alopecia: a Histologic Marker and Pathogenetic Clue

Abstract: Twenty-one of 65 (31%) biopsy specimens from patients with male pattern alopecia demonstrated the presence of individually displaced multinucleate giant cells without a significant concomitant cellular infiltrate. This finding was absent in a diverse group of other forms of alopecia. Whether individually displaced multinucleate cells are a useful histologic marker for diagnosing early stages of androgenetic alopecia remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…1046 Infrabulbar and peri-isthmic inflammation are rare, but when present, this so-called inflammatory variant, with histological features that overlap alopecia areata and Kossard's chronic stem cell folliculitis, may be an indication of reduced response to treatment. 1049 Small nerve networks, resembling encapsulated end organs, may be seen. 1049 Small nerve networks, resembling encapsulated end organs, may be seen.…”
Section: Treatment Of Androgenetic Alopeciamentioning
confidence: 99%
“…1046 Infrabulbar and peri-isthmic inflammation are rare, but when present, this so-called inflammatory variant, with histological features that overlap alopecia areata and Kossard's chronic stem cell folliculitis, may be an indication of reduced response to treatment. 1049 Small nerve networks, resembling encapsulated end organs, may be seen. 1049 Small nerve networks, resembling encapsulated end organs, may be seen.…”
Section: Treatment Of Androgenetic Alopeciamentioning
confidence: 99%
“…In the cell infiltration of the deeper portions of the follicle, a focal foreign-body giant-cell reaction was also observed. The role of the giantcell reaction was unknown in this study, although the presence of giant cells has been demonstrated in patients suffering from alopecia (Domnitz and Silvers, 1979).…”
Section: Discussionmentioning
confidence: 77%